MRI visibility and displacement of elective lymph nodes during radiotherapy in head and neck cancer patients - Reinders, Floris C. J.; Stijnman, Peter R. S.; de Ridder, Mischa; Doornaert, Patricia A. H.; Raaijmakers, Cornelis P. J.; Philippens, Marielle E. P. (Frontiers in Radiology, 2022)
Background To decrease the impact of radiotherapy to healthy tissues in the head and neck region, we propose to restrict the elective neck irradiation to elective lymph nodes at risk of containing micro metastases instead of the larger lymph node volumes. To assess whether this new concept is achievable in the clinic, we determined the number, volume changes and displacement of elective lymph nodes during the course of radiotherapy. Methods MRI scans of 10 head and neck cancer (HNC) patients were acquired before radiotherapy and in week 2, 3, 4 and 5 during radiotherapy. The weekly delineations of elective lymph nodes inside the lymph node levels (Ib/II/III/IVa/V) were rigidly registered and analyzed regarding number and volume. The displacement of elective lymph nodes was determined by center of mass (COM) distances, vector-based analysis and the isotropic contour expansion of the lymph nodes of the pre-treatment scan or the scan of the previous week in order to geographically cover 95% of the lymph nodes in the scans of the other weeks. Results On average, 31 elective lymph nodes in levels Ib-V on each side of the neck were determined. This number remained constant throughout radiotherapy in most lymph node levels. The volume of the elective lymph nodes reduced significantly in all weeks, up to 50% in week 5, compared to the pre-treatment scan. The largest median COM displacements were seen in level V, for example 5.2 mm in week 5 compared to the pre-treatment scan. The displacement of elective lymph nodes was mainly in cranial direction. Geographical coverage was obtained when the lymph node volumes were expanded with 7 mm in case the pre-treatment scan was used and 6.5 mm in case the scan of the previous week was used. Conclusion Elective lymph nodes of HNC patients remained visible on MRI and decreased in size during radiotherapy. The displacement of elective lymph nodes differ per lymph node level and were mainly directed cranially. Weekly adaptation does not seem to improve coverage of elective lymph nodes. Based on our findings we expect elective lymph node irradiation is achievable in the clinic.